ASSESSING INVESTMENT APPEAL OF RUSSIAN REGIONS: METHODOLOGICAL ASPECT - Konstantin V. Basyuk (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The article tries to apply methods of building multifactor industrial functions for solving the problem of assessing the investment appeal of regions in the Russian Federation. As a concrete instrument the author proposes to calculate regressive equation which can allow us to show the form and level of contribution of private factors in the total volume of cash raised in the region. Misbalance of regional development is an acute problem for Russia and many other countries that chose the way of building civilized market economy. Raising foreign capital can become a solution to this problem, as a region excluded from the system of interrelations cannot find a point of growth in order to overcome its economic problems. In the issue of raising capital at the regional level this topic implies the integral assessment of the ability to raise funds. How can it be achieved? Which regional factors can affect it? Can it show the ability of the region to use the money? These methodological questions are discussed in the article, factor analysis, multifactor industrial function, assessing the level of investment appeal of the region.